PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS GOOGLE SITES PADA PEMBELAJAAN SENI RUPA SISWA KELAS V SEKOLAH DASAR - Zahra, Lailatuz; Yunisrul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to address the limited use of technology-based media in fine arts learning, especially in the context of drawing. Many students encounter difficulties in expressing their creativity in drawing, which calls for innovative learning solutions that leverage technology. The objective of this study is to develop a valid, practical, and effective learning medium based on Google Sites for fifth-grade elementary school students. The research follows a Research and Development approach, specifically using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The study was conducted in two schools, UPT SDN 02 Padang Ganting as a trial school and UPT SDN 03 Padang Ganting as a research school. The results of the material validity test were 90%, the results of the media validity test were 96%, and the results of the language validity test were 96% of the three validity tests in the very valid category. The results of the teacher response practicality test obtained a percentage of 94.5% while the results of the student response practicality test amounted to 96% of both results in the very practical category. The effectiveness test results obtained from the pre test and post test showed an increase in both schools. It is concluded that learning media based on Google sites in learning fine arts for grade V elementary school students is valid, practical and effective.